A cascade Claisen rearrangement/o-quinone methide formation/electrocyclization approach to 2H-chromenes. Issue 44 (19th May 2017) - Song, Liyan; Huang, Fang; Guo, Liwen; Ouyang, Ming-An; Tong, Rongbiao
Abstract : A new approach to 8-substituted 2 H -chromenes is developed, featuring a novel cascade aromatic Claisen rearrangement/ o -quinone methide formation/6π-electrocyclization. Abstract : A new approach has been developed for the synthesis of 8-substituted 2 H -chromenes, featuring a novel cascade aromatic Claisen rearrangement/ o -quinone methide formation/6π-electrocyclization. This new method was demonstrated with 28 examples tolerating different substitutions at alkenes, allylic and aromatic ring and with total syntheses of three 2 H -chromene natural products.